Eksplorasi Hambatan Dan Aktivitas Mahasiswa Program Studi Pendidikan Bahasa Inggris Dalam Mata Kuliah Translation - Hariyanti Djafar; Sariwati Muhamad (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims to explored the students’ obstacle in learning translation, increasing the students’ acticity in Translation learning, enhancing lecturer creativity in handle translation study to applied an approppriate method in teaching translation. The method of this study is qualitative which involved 12 respondents of English Department students Bumi Hijrah Tidore. Data was collected by doing observation and interview. It’s found that there are three important points become obstacles for students in learning translation, namely: 1). Student focus on learning is ignored. 2). Fearlessness in questioning in the class when confused with the material. Thus, when lecturers provide excersices, most of them are not able to finished well. 3). Involved in group activities are also still minimal, both group presentation tasks that take place in class or doing assignment. These obstacles were influenced by personality, Learning Motivation, Students’ Acticity in Learning Translation, and Supporting Media in understanding the translation theory such as still depended on google translation. The conclusion of this study is the students should learn and dare to questioning in a team. The lecturer also needed to adapt the method of teaching to please the learners.